PHYTOCHEMICAL ANALYSIS AND TOTAL ANTIOXIDANTCAPACITY OF MULBERRY LEAF (MORUS ALBA L.) - AISYAH, NUR (Journal Medical Universitas muhammadiyah Makassar, 2026)
The mulberry plant (Morus alba L.) is one of the herbal plants that are useful as a phytopharmaceutical. Mulberry leaves are known to be rich in antioxidants that can overcome infections caused by bacteria, fungi, protozoa, antimalaria, and anticancer. This study used adescriptive approach with experimental studies using in vitro techniques and bioassays using Artemia salina larvae. In vitro techniques were used in phytochemical tests, total phenolic tests with Folin-Ciocalteu reagent, and total antioxidant capacity tests using DPPH, ABTS, and FRAP reagents. The research data were analyzed using GraphPad Prism 10 software. The main phytochemicals in mulberry leaves include flavonoid derivatives and phenolic compounds with high antioxidant activity. The total phenolic content, expressed as gallic acid equivalents, was 16,24 mg GAE/g DW. Antioxidant capacity measured by the ABTS method yielded an IC50 value of 22,42 µg/mL, the DPPH assay showed an IC50 value of 343,413 µg/mL, while the FRAP assay indicated an IC50 value of 24,578 µg/mL